An atypical chondroid syringoma with malignant degeneration: Utility of comparative genomic hybridization in confirming the diagnosis. (1st February 2021) - Zia, Shereen; Shaw, Brandon; Chapman, Stephanie; Friedman, Ben J.
Abstract: Chondroid syringoma (CS) represents the cutaneous counterpart of mixed tumor (pleomorphic adenoma) of salivary glands. Definitive diagnosis is made on histopathology and is based on the presence of characteristic epithelial and stromal components. We report a case of an atypical CS arising on the extremity of an elderly male patient. Histomorphologic features of necrosis and cellular atypia raised suspicion for malignant degeneration, an exceptionally rare circumstance in this context. To further support the diagnosis of malignancy, array comparative genomic hybridization was performed from both low and higher grade areas of the tumor. Both regions demonstrated multiple copy number gains and losses, with additional loss of q7p ( TP53 ), loss of 19p, and loss of heterozygosity on16q demonstrated in the more atypical foci. To our knowledge, this is the first case description of malignant degeneration of a CS with correlative microarray analysis. The findings in this case may prove useful in confirming the diagnosis in future ambiguous cases.